A Critical Analysis of Pre-Service Islamic Elementary Teachers’Problem-Solving Abilities in Science Education - Kustiarini; Sarwi; Ani Rusilowati; Novi Ratna Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
The low problem-solving skills of prospective teacher students pose a challenge in preparing educators capable of designing meaningful and contextual science learning. This ability is important because prospective teachers are required to have critical, analytical, and reflective thinking skills in dealing with various learning problems in elementary schools. This study aims to critically analyze the problem-solving abilities of PGMI students in the context of science learning. The study used a descriptive quantitative approach involving 36 sixth-semester PGMI students selected through a purposive sampling technique. Data collection was conducted using a case study-based test developed based on six problem-solving indicators, including defining the problem, diagnosing the problem, formulating alternative strategies, selecting and implementing strategies, evaluating implementation, and determining the implications of science learning. Data were analyzed using descriptive statistics through percentage calculations and distribution of ability categories. The results of the study indicate that students' problem-solving abilities are still in the developing stage. Students tend to be able to identify problems and develop initial strategies for solving them, but still experience difficulties in conducting in-depth problem diagnosis and reflective evaluation of the implemented solutions. This study concludes that there is still a gap between theoretical understanding and practical application of problem-solving skills in science learning. The implications of this research emphasize the importance of systematically strengthening contextual, reflective, and case-based learning in the PGMI curriculum to improve the pedagogical competence of prospective teachers.